PENGARUH MODEL PEMBELAJARAN LOK-R TERHADAP HASIL BELAJAR IPS PESERTA DIDIK PADA MATERI KONFLIK DAN INTEGRASI KELAS VIII DI SMPN 1 SURABAYA - Kristyanto Soni, Herminus; Wirlin Gatas, Ildefonsia; Murwanti, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education in the 21st century aims to produce a young generation who has innovation, the ability to learn and can access information media and technology so that this generation can become agents of change for the nation and state. In this classroom action research (CAR), what is offered is the LOK-R learning model. as a solution to improve students' social studies learning outcomes with material on social conflict and integration in secondary schools. Based on the results of the implementation that has been carried out, the LOK-R learning model can be used to become a solution in improving social studies learning outcomes. The learning process with stages of Literacy, Orientation, Collaboration and Reflection can encourage students to think critically so that students can easily have the ability to manage information and communicate well. Keywords: learning outcomes, LOK-R learning model, social sciences literacy